Development of Design-Oriented Evaluation Tool : A HCI Perspective - Suganthi Naikkar, Subramaniam (2004)
Design-oriented is an alternative method in evaluating multimedia applications based on general usability criteria (as opposed to user-oriented evaluation which is is commonly applied in usability testing). This paper identifies the criteria and dimensions for the design-oriented evaluation. Based on the identified criteria, two version and dimensions for the design-oriented evaluation. Based on the identified criteria two versions of tool (long and short) were created to assist multimedia lecturers to assess their students' projects. Reliability and validity test were conducted to ensure the tool is valid and accurate to use. Suggestion and comments from experts were taken into consideration during the validation test. Certainly, the results show that majority of the experts accept the created tool as a good help in evaluating student's projects without hesitation.